HIV and AIDS knowledge and sexual behaviours amongst secondary school learners in Harare, Zimbabwe - Margaret Mlingo; Valerie J. Ehlers; Janetta Roos (AOSIS, 2012)
Efforts to stem the tide of the Human immunodeficiency virus (HIV) and Acquired immune deficiency syndrome (AIDS) pandemic in Africa emphasise the necessity that learners should be able to make informed decisions. Although learners in Zimbabwe's schools are taught about HIV and AIDS, the extent of their knowledge needed to be determined. The major objective was to assess the knowledge of secondary school learners in Harare, Zimbabwe, about HIV and AIDS. Structured interviews were conducted with 75 Grade 8 (Form 1) secondary school learners from four schools in Harare.Most learners had obtained their HIV and AIDS knowledge from schools, but some did so from their parents, community activities, the radio or television. No learner had commenced with sexual activities and all had heard about HIV, but not all knew what HIV was, and even fewer could define AIDS. Less than one-third of the learners could mention the three most important HIV preventive measures. Most learners were willing to undergo voluntary counselling and testing (VCT), but few had done so. As no learner had commenced sexual activities, opportunities existed to empower Grade 8 (Form 1) learners with adequate HIV and AIDS knowledge. Generally the learners' HIV and AIDS knowledge levels were high but some misconceptions existed. Schools should engage with radio and television programmes to address misconceptions about HIV and AIDS. Learners should be enabled to access VCT services. More effective HIV prevention education in Zimbabwe's schools, could enable more youth to remain HIV negative.